Transforming educator preparation for changing times - Muller, Robert D. (Advances in teacher education., 2024)
"This edited volume explores the progress, challenges, and future prognoses of educator preparation programs (preK-12 and higher education) in the U.S. Using examples drawn from a large, urban-centered college of education, the book provides practical guidance and insights regarding teacher preparation and educational leadership. Edited by former NLU Dean, Robert Muller and authored by NLU National College of Education faculty, the chapters explore how programs that prepare novice teachers, provide advancement opportunities for practicing educators, and develop education leaders have adapted to serve the needs of contemporary school institutions. This work is particularly timely given the myriad of challenges facing the nation's teacher and education leader preparation pipeline, and the critical role colleges of education play in addressing those needs. Primarily focused on leading institutional change in a large, metropolitan college of education, this work will be of interest to colleges of education leaders and faculty, PK-12 and higher education teachers and leaders, policy makers, and the broader teacher preparation and educator development field. Founded in the 1880s, the Chicago-based National College of Education (NCE) at National Louis University serves approximately 3,000 educators annually in its initial and advanced teacher preparation, and educational leadership programs. For its commitments to diversity, inclusion and equity within transformative higher education, National Louis University was recognized as a top 20 school in Washington Monthly's 2022 National University Rankings. After two introductory chapters to set the institutional context, the book is divided into four major sections: In Prepare, the authors explore how a college of education has approached equipping novice teachers for success as they enter the teaching profession. It focuses on the transformation of initial teacher preparation programs to meet the needs of contemporary schools and districts, and profiles the programmatic initiatives to make those changes. In Advance, the authors describe programs that support teachers as they advance in their careers, and the role of continuing graduate education in developing exemplary educators. In Lead, the authors address the challenges facing education leaders and adapting their professional development to equip them to lead. It explores efforts to develop a cadre of leaders across education systems with the requisite knowledge and habits of mind to lead amidst unprecedented change. Finally, Building the Institution addresses several key cross cutting processes that support transformation efforts, including strategy development and implementation, partnership development, technology deployment, human capital development and data utilization"--